Avaliação hidroenergética de sistemas de distribuição de água : suprimento contínuo versus intermitente - Rui Gabriel Modesto de Souza (2021)
Water is an essential element for human survival and for the economic, social and health development of the societies. However, in many regions of the planet, meeting the required demand has become an arduous task due to water scarcity. Despite the scenario of water scarcity, in Brazil, the non-revenue water in Water Distribution Systems (WDS) reached 39.2 % in 2019, which also interferes with the energy consumption of the sector, since part of the pumped volume could be avoided. Pressure control, especially during the night, where the pressure is high, is an effective tool to minimize the problem, owing to the fact that the leakage flow is directly related to this parameter. An alternative solution, is the operation of the system intermittently, which would cause that the actual leakage become null during this period of low consumption and high pressures, when is usually high, since the system does not operate. Due to the existence of tanks in most homes in Brazil, shortage problems would hardly occur during this period. However, it is commonly related to this operation the increased risk of intrusion of pathogens and rupture of the pipe during its filling. Thus, the objective of this work was to raise operational risks and evaluate the hydroenergetic efficiency of the intermittent operation in relation to continuous operation in two case studies, using the benchmarking networks ZJ and OBCL-1. Energy consumption and volume of leaks were considered in obtaining the best operational solution. The results obtained in the continuous operation were confronted with different levels of intermittent, ranging from 12h to 21h of operation, to identify the real economic benefits that intermittency operation can generate from the hydroenergetic point of view. It was also proposed the implementation of Pressure Reducing Valves (PRV) in continuous operation, to improve pressure control, and the replacement of the Trunk Network (TN), at the best level of intermittent operation, to reduce the energy consumption. In each case, the Particle Swarm Optimization (PSO) optimization algorithm was used to select the most appropriate pumps and define its operational routine by adjusting its speed, define the pressure settings of the PRVs, and select the diameters of the TN. Despite the additional caution with water quality, the intermittent operation proved to be a feasible strategy from an economic point of view, achieving a reduction in operating costs of up to 60.9 % for the ZJ network and 47.4 % for OBCL-1 network.